The Effects of Various Water Table Depths on CO2 Emission at Oil Palm Plantation on West Aceh Peat - Etik Puji Handayani; Meine Van Noordwijk; Kamarudin Idris; Supiandi Sabiham; Sri Djuniwati (JOURNAL OF TROPICAL SOILS, 2010)
The Effects of Various Water Table Depths on CO2 Emission at Oil Palm Plantation on West Aceh Peat (EP  Handayani, M van Noordwijk, K Idris,  S Sabiham and S Djuniwati):  Changes in the depth of water table influenced carbon cycling in peatlands, and affected the sources and sinks of carbon dioxide.  The effects of depth of water tables in oil palm plantations on the emission of CO2 were studied. CO2 emissions of peatland were measured in Meulaboh, West Aceh using cylindrical chambers and  air samples from the chambers were analyzed by gas chromatography. Five-point transects perpendicular to drainage canals provided variation in the depth of water tables for the samples. Data from oil palm fields were compared to data from an adjacent swamp forest. The data confirmed that  the increasing depth of water table was accompanied by the increasing in microbial activity that was measured by CO2 emission.  The CO2 emissions from chambers with additional root zones were higher than from bulk soil chambers between one to four times.